Dynamic Changes in the Structure, Chemical State and Catalytic Selectivity of Cu Nanocubes during CO2 Electroreduction: Size and Support Effects. Issue 21 (26th April 2018) - Grosse, Philipp; Gao, Dunfeng; Scholten, Fabian; Sinev, Ilya; Mistry, Hemma; Roldan Cuenya, Beatriz
Abstract: In situ and operando spectroscopic and microscopic methods were used to gain insight into the correlation between the structure, chemical state, and reactivity of size‐ and shape‐controlled ligand‐free Cu nanocubes during CO2 electroreduction (CO2 RR). Dynamic changes in the morphology and composition of Cu cubes supported on carbon were monitored under potential control through electrochemical atomic force microscopy, X‐ray absorption fine‐structure spectroscopy and X‐ray photoelectron spectroscopy. Under reaction conditions, the roughening of the nanocube surface, disappearance of the (100) facets, formation of pores, loss of Cu and reduction of CuO x species observed were found to lead to a suppression of the selectivity for multi‐carbon products (i.e. C2 H4 and ethanol) versus CH4 . A comparison with Cu cubes supported on Cu foils revealed an enhanced morphological stability and persistence of Cu I species under CO2 RR in the former samples. Both factors are held responsible for the higher C2 /C1 product ratio observed for the Cu cubes/Cu as compared to Cu cubes/C. Our findings highlight the importance of the structure of the active nanocatalyst but also its interaction with the underlying substrate in CO2 RR selectivity. Abstract : Cu nanocubes : A variety of in situ and operando spectroscopic and microscopic methods were used to gain insight into the correlation between the structure, chemical state, and reactivity of size‐ and shape‐controlled ligand‐free Cu nanocubes during CO2 electroreduction. Dynamic changes in the morphology and composition of Cu nanocubes supported on carbon were monitored under potential control and correlated with product selectivity.